Tumbuhan dalam Perspektif Ibnu Sina - Mohd. Najmi Adlani Siregar (Al-Ulum: Jurnal Pendidikan Islam, 2022)
This article is written in order to construct plants in the perspective of Ibn Sina which is intended as part of life. The type of writing in the article is qualitative research using library research with content analysis method as a data analysis tool. The description of the results of this article is the soul of plants (an-Nafsul Nabatiyah), which has three powers, namely; (1) eat (nutrition power), (2) grow (growth), (3) reproduce (reproduction).